Digital Transformation in Higher Education Accreditation: Streamlining Self-Evaluation Workflows at Polytechnic Institutions - Pinem, Sanjaya; Tyas, Sari Setyaning; Indera Nata Raharja (Bahasa Indonesia, 2025)
In the landscape of vocational higher education, accreditation is the benchmark for institutional quality and public accountability. However, many institutions, particularly polytechnics, struggle with the administrative burden of manual compliance, characterized by fragmented data and inefficient "chasing documents" cycles. This study explores the digital transformation of the internal quality assurance process at Politeknik Negeri Media Kreatif. By shifting from a manual, paper-based workflow to a centralized web-based self-assessment system, the institution aimed to enhance readiness for National Accreditation Agency for Higher Education (BAN-PT) standards. The research details the re-engineering of the accreditation workflow, utilizing a digital platform that offers real-time gap analysis and centralized evidence management. The results demonstrate that digital intervention significantly streamlines the evaluation process, achieving a practicality score of 78% among stakeholders. This transformation not only simplifies administrative tasks but also fosters a culture of continuous quality improvement.